Spatial-temporal evolution and driving factors of green high-quality agriculture development in China - Huang, Jie; Duan, Xinyu; Li, Yongle; Guo, Hongtao (Frontiers in Environmental Science, 2023)
The fundamental means of addressing the challenges concerning China's agricultural resources and environment is to achieve green and high-quality development within the agricultural sector. In this study, we measured the level of green high-quality agricultural development (GHQAD) in China from 2003 to 2020, and used Theil index, Moran's I and Geographic detector to reveal the evolution trend and driving factors of GHQAD in China. The results show that the development level of GHQAD in China is constantly improving while the spatial difference is decreasing, and the primary contributor to this overall variation is the intra-regional variation. The spatial distribution of GHQAD in China was positively correlated, We have utilized Theil index, Moran's I, and Geographic detector to unveil evolution trend of GHQAD in China and understand the driving factors behind it. Our findings reveal that GHQAD is notably higher in eastern regions, while it's lower in the central and western areas.Importantly, the overall trend indicates a positive trajectory with GHQAD. Furthermore, the variation in GHQAD is showing a declining pattern, and the primary contributor to this overall variation is the intra-regional variation. We've observed a positive correlation in the spatial distribution, with high concentration in eastern and central regions, and low concentration in the central and western regions. Notably, topographic relief degree and urbanization level are the key driving factors contributing to the spatial differences in GHQAD across China. The insights gained from this study will be particularly valuable for the government decision-making processes, thereby elevating GHQAD development in China and ultimately achieving coordinated development within the agricultural sector.